Effect of water-based cooling on PV performance: case study - Shaaban, Abdullah M. A.; El-Samahy, Adel A.; Abed, Kamal A.; Mosa, Magdi A. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Solar energy, especially photovoltaic (PV), is one of the most common renewable energy resources. Panel temperature and dust are the common problems which have a great effect on the conversion performance of PV. These problems can be alleviated by cooling and cleaning in order to improve its efficiency. This paper investigates the effect of PV cooling on the energy harvesting. The study is carried out experimentally using two similar PV panels which are subjected to the same environmental conditions and connected to similar load. The proposed cooling system is applied to one of these panels while the other is left without cooling for comparison. Five cases of water cooling are tested; surface cooling in two ways, back cooling using sprayers with and without cotton net, and hybrid cooling. The effect of cooling can be noticed from the measured load voltage and power. It is found that the surface cooling is the most effective because it achieved the best improvement comparing to others. When the panel temperature decreased from 65 to 42 °C, the load voltage increased from 32.55 to 35.8 V and the load power from 4.57 to 5.37 watts, with an improvement of about 10% and 18%, respectively.